Game on for health: designing gamified campaigns to drive behavioral change - Nurul Hidayah Mat Zain; Anita Mohd Yasin; Zainab Othman; Siti Nuramalina Johari; Norshahidatul Hasana Ishak; Siti Rahayu Abdul Aziz (Intelektual Pustaka Media Utama, 2026)
An awareness campaign aims to reach out to the public, measure the outreach accurately, and motivate the public to act. In other words, awareness campaigns deliver messages on the importance and effects of the promoted event to the audience. However, studies that examine the users’ perception of design for behavior change through gamified health awareness campaigns are limited, especially in combating the coronavirus disease 2019 (COVID-19) outbreak. Subsequently, analysis of such perceptions is crucial in supporting game designers in developing engaging games for health awareness campaigns. Thus, the current study explores users’ perceptions based on elements in the GAMEBC Model: Autonomy, Relatedness, Competence, and Engaging. A total of 180 students from UiTM Cawangan Melaka (UiTMCM), Jasin Campus, participated in the study. The data was evaluated using conventional descriptive statistical methods. The findings revealed users’ perceptions of the design for behavior change in the context of a gamified health awareness campaign. The study offers a valuable understanding of the necessity of creating a comprehensive gamified campaign that promotes behavioral change for improved quality of life.